Analysis of Instrinsic Factors Affecting Stunting Events of Tools Aged 24-59 Months in the Region of Pulung Village, Ponorogo Regency - Yenny Puspitasari; Katini (Journal for Quality in Public Health, 2022)
Background: The research results of the 2019 Indonesian toddler nutritional status study (SSGBI) noted that the number of stunting toddlers in Indonesia currently reaches 27.67 percent. Toddlers who experience stunting increase the risk of declining intellectual abilities, inhibiting motor skills, productivity, and increasing the risk of degenerative diseases in the future. Objective: To analyze the intrinsic factors of stunting in toddlers aged 24-59 months in the Pulung Village area, Ponorogo. Methods: Quantitative research using a cross sectional approach. Samples were collected by means of purposive sampling technique, as many as 162 mothers of toddlers aged 24-59 months in the pulung area. Results: The most influential intrinsic factor on the incidence of stunting in toddlers aged 24-59 months. Based on the beta value and p value, it was found that the KEK history variable had a value < i.e. 0.000 and a beta value of -.280, then the most dominant variable was the history of SEZ. Conclusion: The most influential factor is the mother's history of KEK. In this case, it is necessary to hold socialization about the importance of maternal nutrition in an effort to prevent the occurrence of SEZ pregnant women to the catin class.